Text Genetics in Literary Modernism and other Essays - Walter Gabler, Hans (Open Book Publishers, 2018)
"This collection of essays from world-renowned scholar Hans Walter Gabler contains writings from a decade and a half of retirement spent in exploration of textual criticism, genetic criticism, and literary criticism. In these sixteen stimulating contributions, he develops theories of textual criticism and editing that are inflected by our advance into the digital era; structurally analyses arts of composition in literature as well as music; and traces the cultural implications discernible in book design, and in the societal processes of the canonisation of works of literature and their authors. Distinctive and ambitious, these essays move beyond the development of concerns voiced in the community of critics and scholars. Gabler responds innovatively to the issues involved and often endeavours to re-think their urgencies through allowing orthodox tenets of national schools of textual criticism to converge and merge. He moves between a variety of topics, ranging from fresh genetic approaches to the work of James Joyce and Virginia Woolf, to significant contributions to the theorisation of scholarly editing in the digital age. Written in Gabler's fluent style, these rich and elegant compositions are essential reading for literary and textual critics, scholarly editors, readers of James Joyce, New Modernism specialists, and all those interested in textual scholarship and digital editing within the encompassing framework of Digital Humanities."